Structural and functional characterization of the gamma 1 subunit of GABAA/benzodiazepine receptors. - Ymer, S (1990)
The GABAA receptor gamma 1 subunit of human, rat and bovine origin was molecularly cloned and compared with the gamma 2 subunit in structure and function. Both gamma subunit variants share 74% sequence similarity and are prominently synthesized in often distinct areas of the central nervous system as documented by in situ hybridization. When co-expressed with alpha and beta subunits in Xenopus oocytes and mammalian cells, the gamma variants mediate the potentiation of GABA evoked currents by benzodiazepines and help generate high-affinity binding sites for these drugs. However, these sites show disparate pharmacological properties which, for receptors assembled from alpha 1, beta 1 and gamma 1 subunits, are characterized by the conspicuous loss in affinity for neutral antagonists (e.g. flumazenil) and negative modulators (e.g. DMCM). These findings reveal a pronounced effect of gamma subunit variants on GABAA/benzodiazepine receptor pharmacology.